2016
DOI: 10.17645/pag.v4i1.468
|View full text |Cite
|
Sign up to set email alerts
|

Looking for the European Voter: Split-Ticket Voting in the Belgian Regional and European Elections of 2009 and 2014

Abstract: While European elections are often seen as remote from EU issues, considerations specifically linked to the EU came to the forefront in the wake of the 2014 European elections: the economic and financial crisis, the new process of designation of the European Commission President, and the alleged increase of Eurosceptic votes. This increased salience of political debates about the EU asks for a reconsideration of the 'second-order nature' of European elections. In this context, as in 2009, the Belgian electorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…As voting is compulsory, the exceptional turnout of 88.5% is a bad indicator of the salience of the election. But from the near absence of European campaigns and candidates from public debate and media, as well as from the marginal differences in the election results between the three levels, we may read the EP election as being again overshadowed by national campaigns and candidates (Kelbel et al, 2016). Nevertheless, this competition had a European dimension, as it was dominated by two transnational issues: the climate and migration.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As voting is compulsory, the exceptional turnout of 88.5% is a bad indicator of the salience of the election. But from the near absence of European campaigns and candidates from public debate and media, as well as from the marginal differences in the election results between the three levels, we may read the EP election as being again overshadowed by national campaigns and candidates (Kelbel et al, 2016). Nevertheless, this competition had a European dimension, as it was dominated by two transnational issues: the climate and migration.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…There was no Belgian candidacy for the Spitzenkandidaten procedure. In 2014, the candidacy of Guy Verhofstadt for the Presidency of the Commission had attracted at least some attention to the European election (Kelbel et al, 2016). conclusion Altogether, the EP election went by without much notice.…”
Section: Resultsmentioning
confidence: 99%
“…To test the second order model, Kelbel, van Ingelgom and Verhaegen (2016) make use of the fact that the 2014 EP elections were held on the same day as regional elections in Belgium. As a consequence of the federalisation of Belgium, many important policies are decided at the level of the two regions Wallonia and Flanders, so that these regional elections can be considered to be (near) first order elections.…”
Section: Theme 3: Electoral Behaviourmentioning
confidence: 99%
“…For example, in a study of concurrent regional and EP elections in Belgium in 2009, Van Aelst and Lefevere (, 20) found that indecisive voters were more likely to ticket‐split, reasoning that voters might consider a vote in the EP elections serving as ‘a second‐best option’. Finally, studies have shown that voters who prefer a particular candidate are more likely to split‐ticket vote (e.g., Kelbel et al ) and that contextual factors, such as electoral and party systems, can influence the likelihood that voters ticket‐split (e.g., Plecia ).…”
Section: Split‐ticket Voting In Multilevel Electionsmentioning
confidence: 99%
“… The introduction of ‘ spitzenkandidaten ’ in the 2014 EP elections were intended to increase the saliency of the elections and had some effect on the vote choice of voters that could vote directly for one of the candidates (Kelbel et al ). This was not the case in Sweden, however, and the spitzenkandidaten were largely absent from the Swedish debate preceding the election, making it unlikely that it would have affected voters’ opinions about what was at stake in the elections to any larger degree.…”
mentioning
confidence: 99%